Endometriosis - Pathogenesis, diagnosis and treatment - Piotr Kwiatkowski; Konrad Gładysz; Justyna Szydłowska; Olga Żuchnik; Olgierd Król; Beata Kuczyńska; Magdalena Czelej; Aleksander Kłos; Krzysztof Gieroba; Marcin Szydłowski (Kazimierz Wielki University, 2023)
Introduction: Endometriosis is defined as a chronic gynecological disease characterized by endometrial tissue outside the uterus. The condition affects 5-10% of women of reproductive age worldwide and is associated with pelvic pain and infertility. Despite its prevalence, diagnosis is usually delayed for many years which postpones the introduction of appropriate treatment. Aim of the study: Summary of the current state of knowledge on endometriosis, analyzing the pathogenesis, the current diagnostic approach, highlighting the problem of fertility in this disease entity and presenting treatment options. Methods and materials: A review of the literaturę available in the PubMed database and GoogleScholar from the last 5years was conducted,using the following keywords: endometriosis", "endometriosis pathogenesis", "endometriosis diagnosis", "infertility in endometriosis", "endometriosis treatment" Results: Among the etiological factors mentioned are congenital, environmental, epigenetic, autoimmune and allergic factors. The main theory for the formation of the condition is retrograde menstruation through the fallopian tubes into the peritoneal cavity and implantation of endometrial cells. Laparoscopy is nowadays the gold standard for diagnosis, but less invasive methods that can shorten the time to diagnosis are being sought. Current treatment is limited to surgery, hormonal treatment and analgesics which are associated with many side effects. Conclusion: Endometriosis is the cause of infertility, chronic pain and reduced quality of life in many women. Non-invasive diagnostic tests such as imaging studies, genetic tests, biomarkers or miRNAs have diagnostic potential but more analysis is needed to be applied in daily clinical work. Future research should focus on learning and understanding the pathogenesis, identifying subtypes of the disease, and a modern approach to diagnosis and comprehensive treatment taking into account concomitant general symptoms.